Teaching Materials Using the Discovery Learning Learning Model to Facilitate the Mathematical Communication Skills of Junior High School Students - Nurul Shaqila; Zetriuslita (Jurnal Pendidikan Indonesia, 2023)
Indonesian students are in the low category where students only have basic mathematical abilities. It is caused by difficulties in learning mathematics in the circle material, requires teacher creativity in developing learning, namely in terms of teaching materials, media, and methods used in the learning process. Learning materials that are integrated with good learning models are needed to facilitate students in learning mathematics. Therefore this study aims to develop teaching materials using the discovery learning model to improve students' mathematical abilities in the circle material for class VIII junior high school. This type of research is development research with reference to the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The subjects of this study were teachers and students of class VIII junior high school. Based on the subject teacher and student questionnaires, it can be concluded that the teaching materials have good criteria. Students' response to the media was positive, this can be seen from the value of students' positive responses which reached 83.83%. When viewed from the students' mathematical abilities, it can be said to be quite good, that is, seen from the score of the students' completeness test results reaching 44%. Based on all this, it can be concluded that these teaching materials can facilitate the improvement of students' mathematical abilities.